Developing R&D Portfolio Business Validity Simulation Model and System - Hyun Jin Yeo; Kwang Hyuk Im (The Scientific World Journal)
The R&D has been recognized as critical method to take competitiveness by not only companies but also nations with its value creation such as patent value and new product. Therefore, R&D has been a decision maker’s burden in that it is hard to decide how much money to invest, how long time one should spend, and what technology to develop which means it accompanies resources such as budget, time, and manpower. Although there are diverse researches about R&D evaluation, business factors are not concerned enough because almost all previous studies are technology oriented evaluation with one R&D technology based. In that, we early proposed R&D business aspect evaluation model which consists of nine business model components. In this research, we develop a simulation model and system evaluating a company or industry’s R&D portfolio with business model point of view and clarify default and control parameters to facilitate evaluator’s business validity work in each evaluation module by integrate to one screen.